Static and Time History Earthquake Analysis of LPG Spherical Steel Tanks in Iraq (University of Thi-Qar Journal for Engineering Sciences, 2019)
Spherical storage tanks are widely used in Iraq for store hazardous liquid petroleum gas LPG which, thus it must be adequately designed for seismic actions. This paper present  static and time history analysis of LPG tanks in Iraq using UBC97 code. The time history analysis accomplished by using three artificial earthquakes generated using SIMQKE_GR program in additional to El Centro earthquake records scaled according to PGA. The investigations were performed on the tank in Maysan province which was selected to be representative the other tanks in Iraq due to recently seismic activity in Maysan. The study comprised finite element modeling using STAAD Pro program for the estimation of the dynamic and static responses of the tank structure. The study is performed for both conditions of empty tank and at operating with 100%  fill of LPG. The description of the properties and allowable stresses LPG tank used in Iraq is presented. Its concluded that time history analysis govern the tank behavior. The dynamic magnification factor of 1.4 for displacements and stresses was obtained which reflect the importance of dynamic analysis. The stresses of columns and sphere are within allowable limits except at sphere/column connection which slightly exceed the allowable limit, while the stresses in diagonal bracings are exceed the yielding limit thus double angle section is inadequate